Evaluating the efficacies of Maximum Tolerated Dose and metronomic chemotherapies: A mathematical approach - Guiraldello, Rafael T. [UNESP]; Martins, Marcelo L.; Mancera, Paulo F. A. [UNESP] (Elsevier B.V., 2016)
We present a mathematical model based on partial differential equations that is applied to understand tumor development and its response to chemotherapy. Our primary aim is to evaluate comparatively the efficacies of two chemotherapeutic protocols, Maximum Tolerated Dose (MTD) and metronomic, as well as two methods of drug delivery. Concerning therapeutic outcomes, the metronomic protocol proves more effective in prolonging the patient's life than MTD. Moreover, a uniform drug delivery method combined with the metronomic protocol is the most efficient strategy to reduce tumor density. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Mathematical oncology; Cancer; Tumor-induced angiogenesis; Chemotherapy